2018
DOI: 10.1136/sextrans-2017-053515
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with anal cancer screening follow-up by high-resolution anoscopy

Abstract: Three-quarters of patients with HSIL did not have follow-up HRA within the clinic's recommended follow-up period of 6 months following HSIL diagnosis by HRA. Future studies ought to explore whether addressing anal health during other STI-related care helps improve adherence to recommended time intervals for follow-up HRA. Given the high prevalence of STI and PrEP use, studies might also evaluate whether integrating HRA follow-up with other sexual health screenings helps improve adherence to recommended HRA fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In addition, the incidence of HPV-related anal and head and neck cancers is rising steadily in Europe and North America ( 3 , 4 ). Guidelines for screening of HPV-associated cancers are based on cervical cytology and HPV DNA testing ( 5 ) and on anal cytology and high-resolution anoscopy for anal cancer screening in high-risk groups (e.g., HIV patients among men who have sex with men [MSM]) ( 6 , 7 ). In contrast, for head and neck cancers, there is still a lack of validated screening tools for the identification of HPV-driven cancers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the incidence of HPV-related anal and head and neck cancers is rising steadily in Europe and North America ( 3 , 4 ). Guidelines for screening of HPV-associated cancers are based on cervical cytology and HPV DNA testing ( 5 ) and on anal cytology and high-resolution anoscopy for anal cancer screening in high-risk groups (e.g., HIV patients among men who have sex with men [MSM]) ( 6 , 7 ). In contrast, for head and neck cancers, there is still a lack of validated screening tools for the identification of HPV-driven cancers.…”
Section: Introductionmentioning
confidence: 99%
“…A San Francisco-based study of 246 patients with anal HSIL (79% PWH or with other immunocompromise) found that less than 20% underwent treatment from 1996 to 2006 [23]. A slightly higher number (50 of 155 or 32%) of anal HSIL patients (72% of whom were PWH) from a Boston cohort followed up within 6 months of diagnosis [24]. Another New York-based cohort study of MSM with and without HIV found that although 90% of anal HSIL patients received treatment within 65 days of HRA, 35% were lost to follow-up within 1 year [25].…”
Section: Discussionmentioning
confidence: 99%
“…Research on HRA attendance and acceptability largely focuses on retrospective studies of clinic populations [710]. Prospective studies of HRA attendance, particularly examining factors such as HIV status and race/ethnicity, are limited.…”
Section: Introductionmentioning
confidence: 99%